The influence of Simon Stevin (1548-1620) principles on dutch towns and buildings outside the Netherlands: Case study of Melaka / Robert C.M. Weebers - Weebers, Robert C.M. (2012)
This research concentrates on the influence of the Dutch architect and mathematician Simon Stevin (1548-1620). Stevin's ideas on forts, town planning and buildings are laid down in treatises and have had a great influence on the construction of forts in the Netherlands and forts and outposts of the VOC/Dutch in Asia specifically in East Indies, India, Sri Lanka and Malaya (Melaka). The objectives of this research are: to study and clarify Dutch architectural principles to establish new towns (settlements) outside the Netherlands. Specifically in East Indies India, Sri Lanka, and Malaya (Melaka). To study the implementation of Dutch treatise principles on the fort and settlement of Melaka and to analyse whether Dutch principles were applied on the architecture of Dutch buildings in Melaka in particular on the design of the front facade. The methodology of the research is as follows: The first step was to inventorise what kind of literature would contribute and give a base to the study. The second step was to find material in archives which would support the study. The principles (treatises) of Simon Stevin (1548-1620) were looked into according to which Dutch settlements were designed and the implementation of these on settlements in Southeast Asia. Also documents were studied in which decisions were taken about Melaka concerning changes which were made on the town and the fort during the Dutch era. The third step was to make a general inventory of the public buildings and shop houses in the Core and Buffer Zone of Melaka. From this inventory 9 case studies emerged with regard to the public buildings, the fort and 37 with regard to the shop houses. The findings of this research are that Dutch architecture in Melaka, in the public buildings, shows an exactitude and symmetry in design. As can be seen in the symmetrically placed bays and windows. This study has classified 37 shop houses according to placement of doors and windows in the facade of the shop houses. The study has been conducted by determining architectural characteristics and elements that are essentially of Dutch origin.